2015
DOI: 10.1007/s10802-015-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Unfazed or Dazed and Confused: Does Early Adolescent Marijuana Use Cause Sustained Impairments in Attention and Academic Functioning?

Abstract: There is some suggestion that heavy marijuana use during early adolescence (prior to age 17) may cause significant impairments in attention and academic functioning that remain following sustained periods of abstinence. However, no longitudinal studies have examined whether both male and female adolescents who engage in low (less than once a month) to moderate (at least once a monthly) marijuana use experience increased problems with attention and academic performance, and whether these problems remain followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
4
31
1
1
Order By: Relevance
“…Boys who scored in the top 30% and an approximately equal number randomly selected from the remainder were selected for follow-up ( N = 503). The follow-up sample did not differ significantly from the screening sample on race, family composition, and California Achievement Test reading scores (Pardini et al, 2015). The boys’ mean age at screening was 6.9 ( SD = 0.5).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Boys who scored in the top 30% and an approximately equal number randomly selected from the remainder were selected for follow-up ( N = 503). The follow-up sample did not differ significantly from the screening sample on race, family composition, and California Achievement Test reading scores (Pardini et al, 2015). The boys’ mean age at screening was 6.9 ( SD = 0.5).…”
Section: Methodsmentioning
confidence: 82%
“…It is critical to differentiate adolescence-limited from continuing users because some negative effects of regular marijuana use (e.g., cognitive impairment) can rebound following periods of sustained abstinence (see Pardini et al, 2015), and cumulative exposure may be more critical to the development of long-term problems than age of onset (Labouvie & White, 2002; Meier et al, 2012). Thus, if we can identify early risk factors that increase the probability of continued use, we may be in a better position to intervene before problems develop.…”
Section: Introductionmentioning
confidence: 99%
“…There is tentative evidence that there may be causal effects in the other direction (i.e., substance use leading to an increase in ADHD symptoms) 24,25 . In monozygotic twin pairs discordant for smoking, the smoking twin scored higher on attention problems -a difference which only appeared after smoking was initiated 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Frequent cannabis use before the age of 16 predicted significantly higher rates of substance use, delinquency, unemployment, and educational difficulties among teens (Fergusson & Horwood, 1997). By contrast, Pardini et al (2015) found no association between EAOM (defined as <17 years) and adolescent attention problems or academic performance, although this might reflect the fact that their subjects had low to moderate levels of use and were past the age when marijuana use becomes normative.…”
Section: Introductionmentioning
confidence: 63%